2020
DOI: 10.1111/aogs.13827
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for poor neonatal outcome in pregnancies with decreased fetal movements

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
1
19
2
Order By: Relevance
“…However, the respondents reported there were factors affecting the implementation of guidelines, such as language barriers [41]. In a previous study of women seeking medical care for reduced foetal movements published by our research group in 2020, [42] it was found that in a very large percentage of stillbirths reduced foetal movement was the symptom of intrauterine death.…”
Section: Causes Of Deathmentioning
confidence: 99%
“…However, the respondents reported there were factors affecting the implementation of guidelines, such as language barriers [41]. In a previous study of women seeking medical care for reduced foetal movements published by our research group in 2020, [42] it was found that in a very large percentage of stillbirths reduced foetal movement was the symptom of intrauterine death.…”
Section: Causes Of Deathmentioning
confidence: 99%
“…They also concluded that in this sample of women there was a higher frequency of low Apgar Score <7 at 5min: (3,3%), a higher frequency of low pH in umbilical cord blood (2,9%) and more babies had to be admitted in the NICU (3,9%). Additionally SGA fetuses had a significantly higher risk of stillbirth than normal fetuses ( 34 ).…”
Section: Resultsmentioning
confidence: 95%
“…Sterpu et al, ( 34 ) performed a retrospective cohort study and investigated the outcome of 3243 pregnancies presenting with reduced fetal movements. They concluded that the risk of stillbirth in pregnancies with reduced fetal movements is five times higher than in normal pregnancies ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations